Heat transfer computation for crude oil flow along pipeline - Siti Amirah, Nal (2014)
The waxes that present in most crude oils include n-alkanes, iso-alkanes, alkyl cyclic compounds and alkyl aromatic. The amount of wax contained in the crude oil sample varies. The deposition of the waxes is responsible for some of the issues may result in production shutdowns and others. The wax appearance temperature (WAT) is the temperature at which, on a cooling cycle, the crude oil first precipitates solid wax. The position of the Wax Appearance Temperature (WAT) of crude oil in pipeline was determined. From the temperature of surrounds, heat conduction and convection equation are used to determine the temperature of the crude oil inside the pipeline based from different depth. It was compared with Wax Appearance Temperature (WAT) from different Crude Oil. The Crude Oils are from South China Sea, Penara and Larut Malaysia, Algeria, Libya, Iran and Venezuela. All the calculation was used FORTRAN. The Wax Appearance Temperature (WAT) of every Crude Oil was identified. Result from the calculation showed that the depth of Wax Appearance Temperature in the pipeline for every crude oil from South China Sea, Penara, Larut, Algeria, Libya, Iran and Venezuela, Angola, Syria, Gabon, Tunisia and France are 1.20253km, 2.10420km, 1.65920km, 1.35587km, 1.80920km, 1.64920km, 1.19829km, 1.98920km, 1.65587km, 1.89920km, 2.26587km and 1.67253km respectively. The depth of Wax Appearance Temperature (WAT) from Tunisia is deepest compare to other origin of Crude Oil